ISSUES OF DEVELOPING GRAMMATICAL AND LEXICAL SKILLS IN MEDICAL STUDENTS (Eureka Journal of Language, Culture & Social Change, 2026)
The development of grammatical and lexical skills is one of the central challenges in teaching English to medical students. Since future healthcare professionals are expected to communicate accurately, interpret specialized texts, and participate in academic and clinical discourse, language instruction in medical education must address both general linguistic competence and domain-specific communicative needs. This article examines the main issues involved in developing grammatical and lexical skills in medical students and identifies the pedagogical conditions that influence this process. The study employed a qualitative classroom-based approach, including observation of medical English classes, analysis of student written work, vocabulary tasks, and reflective feedback from learners. The findings reveal that medical students commonly experience difficulty in mastering professional terminology, using grammar accurately in context, distinguishing between general and specialized vocabulary, and transferring passive vocabulary into active speech. In addition, interference from the native language, limited communicative practice, and the density of medical discourse often slow down language acquisition. The discussion emphasizes that grammatical and lexical competence should not be taught separately but integrated through contextualized, profession-oriented tasks. The article concludes that the most effective way to develop these skills is through systematic exposure to authentic medical texts, repeated vocabulary recycling,grammar instruction linked to clinical communication, and task-based learning that reflects real professional situations.
Keywords: Grammatical skills, lexical skills, medical English, professional communication, ESP, vocabulary development, grammar instruction.